Prevalence of antimicrobial resistance in three poultry farming systems within the UK and use of anaerobic digestion as a sanitation measure - Guest, Sarah (2024)
Antimicrobial resistance (AMR) is considered one of the greatest threats to human health. Livestock manure is known to be a hotspot for antibiotic residues, antibiotic resistant bacteria (ARB), antimicrobial resistance genes (ARGs), mobile genetic elements (MGEs) and co-selecting agents. This is often spread onto land as a fertiliser, allowing AMR to enter the environment, potentially contaminating land, wild animals, pets (e.g. dogs), waterbodies, the food chain, and ultimately humans (via consumption and recreational activities). Sound manure management is essential to prevent the spread of environmental AMR associated with livestock farming. This study determined the prevalence of antibiotic resistant Enterobacteriaceae in the litter of three contrasting poultry farming systems (layers, broilers and back-yard hens) in the UK, and laboratory scale anaerobic digestion (AD) was carried out on litter from these systems. High-throughput qPCR was used to determine the fate of 96 ARGs/MGEs during AD, and 16S amplicon sequencing was used to determine changes in the bacterial and archaeal community structure during AD. Multidrug resistant Enterobacteriaceae were found in the litter from all three farming systems. Sixty-three ARGs/MGEs were detected across the three farming systems, and relative abundance (RA) of 37 of these was significantly affected by AD. The RA of other genes, such as intI1, was unaffected by AD. Firmicutes, Proteobacteria, Actinobacteriota and Bacteroidota were the dominant phyla in all poultry litters and during mesophilic AD. The genera Oceanisphaera, Lactobacillus, Corynebacterium, Bacteroides, Pseudomonas, Enterococcus, Jeotgallicoccus and Staphylococcus were present during AD of all litters, and Methanobrevibacter was the most abundant archaeal genera. The prevalence of ARGs and MGEs detected in this study highlights the need for poultry litter sanitation before land application. This study also provides a comprehensive insight into the behaviour of ARGs and MGEs during mesophilic AD of different poultry litters, and demonstrates that behaviour varies depending on starting litter and individual ARG/MGE. This work outlines that using one sanitation method carried out under the 3 same operating conditions is ineffective at reducing the abundance of ARGs and MGEs in poultry litter obtained from different farming systems.